PENANAMAN BUDAYA DISIPLIN TERHADAP PESERTA DIDIK KELAS VI MIS GUPPI LAIKANG KECAMATAN KAJANG KABUPATEN BULUKUMBA - Yusdiani, Nurmila; Sulaiman, Umar; Seknun, Yusuf (Inspiratif Pendidikan, 2018)
This journal discusses the cultivation of a culture of discipline towards students of class VI MIS GUPPI Laikang, Kajang District, Bulukumba Regency. The type of this research is descriptive qualitative and the research subject is students. Data collection techniques used in this study are observation guidelines and interview guidelines. Analysis of the data used in this study is data reduction, data presentation and conclusion.Based on the results of data analysis using qualitative descriptive analysis, it was stated that (1) forms of disciplinary culture including students wearing complete uniforms, students entering class on time, students lining up before entering class, students carrying complete learning equipment, students doing assignments well, students do not eat and drink in class, the hair of male students is cut short, students do not make noise if it has nothing to do with the lesson, students have good manners, students do not leave seats if there is no need, participants students do not dispose of garbage in the classroom, students maintain neatness in clothes, students ask permission from the teacher when they want to leave the class, students do not speak when the teacher is explaining; (2) The school has instilled a culture of discipline by fulfilling the elements of discipline, namely, making regulations, teaching habits, giving punishments, giving awards and setting examples; (3) factors that hinder the cultivation of disciplinary culture, namely family environment factors (parents), and how to overcome them, namely by giving penalties, giving warnings and giving awards so that students are motivated to behave discipline.